Chapter Sostenibilità e riproduzione del capitale territoriale: il problema della scala di analisi - Rocchi, Benedetto (Territori, 2020)
Starting from a critique of the concept of "natural capital" which helps in defining the concepts of territorial and rural capital, the utility is affirmed of measuring the sustainability of individual and collective actions with respect to the contribution they offer to their production and reproduction. The analysis of case studies therefore poses the problem of over-exploitation of territorial capital in the absence of adequate investments for its reproduction. This requires a detailed evaluation of the eco-territorial services, focusing on the communities of actors who take care of them.